‘The translator’s extraordinary artistry’. An Interview with Magdalena Heydel, Conducted by Karolina Król - Król, Karolina (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The interview focuses mostly on Stanisław Barańczak’s methods of translation and his translation oeuvre. Similarities between Polish and American literary life also play a significant role in the text. Another important issue is Barańczak’s and Czesław Miłosz’s correspondence which has not been fully published and remains stored in Beinecke Library archives.